Knowledge adult ICU multiprofessionals team about palliative care (Research, Society and Development, 2023)
The Intensive Care Unit (ICU) functions as a space for advanced life care and offering biopsychosocial assistance to patients in need of Palliative Care (PC). This study aimed to analyze the knowledge of multidisciplinary teams in adult ICUs about PC. This is a cross-sectional, analytical and quantitative study, carried out in a large public hospital in the state of Bahia. Data were collected from March to June 2023, using an electronic questionnaire and analyzed using the Statistical Package for the Social Sciences (SPSS) software version 24.0. 110 health professionals working in adult ICUs participated, with a higher frequency of females (84.5%) and physiotherapists (34.5%). The average age of the participants was 35.7 years. The majority of the sample declared having experience with patients undergoing palliation (77.3%) and 12.7% had completed short or long-term courses, postgraduate studies or another modality in the area of PC. It was found that most professionals understand that medical treatment does not have priority in the PC process, inferring that multidisciplinary techniques and knowledge are important in patient care, without there being superiority between categories.